The importance of the architect’s interpretation and creative ability in «Los ratones de fray Martín» and «Al pie de la letra» in Ricardo Palma’s Tradiciones peruanas - Muguruza Salinas, Emir Enrique (2021)
This article will detail the results of the research on «Los ratones de fray Martín» and «Al pie de la letra», texts that form part of the Tradiciones peruanas, a representative work of the narrator Ricardo Palma. We are interested in emphasising the relationship between the creative ability and interpretation of the personages Friar Martín and Captain Paiva and the professional profile of the nineteenth-century career in architecture, as creative ability and interpretation are part of the profile of today’s architect. The text will also analyse the importance of the creative ability and interpretation that the contemporary architect must possess.